Penurunan Level Nyeri Melalui Terapi Musik pada Pasien Terpasang Ventilasi Mekanik - Herlina, Herlina; Waluyo, Agung (Journal of Telenursing (JOTING), 2024)
This study aims to identify the effectiveness of music therapy in reducing the pain level in patients on mechanical ventilation. The research method used is a systematic review through searching articles on the ClinicalKey Nursing, Scopus, Embase, EBSCOHost databases and hand searching. The research result showed that 7 research articles reported that music therapy was able to reduce pain level in patients on mechanical ventilation. Music therapy lasting 30 minutes and using music with a tempo of 60-80 bpm has a positive effect in reducing pain. In conclusion, music therapy has been proven to be effective in reducing pain level in patients on mechanical ventilation so that it can be applied as a non-pharmacological intervention option in dealing with pain. Keywords: Pain, Music Therapy, Mechanical Ventilation